Research in Hard-to-Reach Populations: Challenges and Strategies for Conducting Sexual Violence Studies in Applicants for International Protection Beyond the European General Data Protection Regulation - Lotte De Schrijver; Adina Cismaru Inescu; Bastien Hahaut; Christophe Vandeviver; Laurent Nisen; Ines Keygnaer (Kerman University of Medical Sciences, 2022)
Background  Conducting research in hard-to-reach populations such as applicants for international protection (AIPs) brings along a number of research challenges. This is especially true for sexual violence (SV) research. Methods  We developed a study design with the intent to reach AIPs in a randomized and anonymous manner including potential illiterate respondents as well, while avoiding as much bias as possible. However, this method was developed just before the entry into force of the new European General Data Protection Regulation (GDPR), upon which important new research challenges emerged. Results  This paper describes the original study design developed to estimate SV prevalence in AIPs in Belgium. We discuss the impact of the GDPR on the recruitment strategy applied to conduct a survey on SV in a randomly selected sample of AIPs, the adapted approach to conduct the study beyond GDPR and lessons learned for future research on sensitive topics in hard-to-reach populations such as AIPs. Conclusion  To achieve reliable prevalence numbers and provide high-quality data on SV in AIPs while respecting the GDPR regulations, studies will require an approach that has become significantly more time consuming and resourceintensive to implement.